{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

File0028

# File0028 - Section 3.2 Differentiation Rules for...

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Section 3.2 Differentiation Rules for Polynomials, Exponentials, Products, and Quotients 50. (a) y = x3 — 3x — 2 :> y’ 2 3x2 — 3. For the tangent to be horizontal, we need In : y’ z 0 :> 0 : 3x2 — 3 => 3X2 : 3 => x = :l: 1. When x : ~l, y : 0 :> the tangent line has equation y = O. The line perpendicular to this line at (—1,0) is x : —1. When x = 1, y : —4 :> the tangent line has equation y = —4. The line perpendicular to this line at (17 —4) is x = l. (b) The smallest value of y’ is -3, and this occurs when x = 0 and y = -—2. The tangent to the curve at (0, —2) has slope —3 => the line perpendicular to the tangent at (0, —2) has slope % => y + 2 = % (x — 0) or y : % x — 2 is an equation of the perpendicular line. _ 4x 91 _ (x2+l)(4)—(4x)(ZX) 4x2+4—8x2 4(—x2+1 _ _ r g «0+ 1) 51. y m —s dx (KM—5,— 0&2“)? _ (XZ+IJT1.thnx—0,y—Oandy _ 1 = 4, so the tangent to the curve at (0,0) is the line y : 4x. When x : 1, y z 2 => y’ = 0, so the tangent to the curve at (l, 2) is the line y = 2. _~ g _ x2+4)(0)—8(2x) _ —16 _ _ _ 716(2) _ 1 52, y m —\ y’ ( (X2+4)7— (“+13% When x —. 2, y _ l and y’ _ (2H4)? _ — 5, so the tangent line to the curve at (2, 1) has the equation y — l = — % (x — 2), or y : — g + 2. 53. y = ax2 + bx + 0 passes through (0,0) :> 0 = a(0) + b(0) T c :> c : O; y 2 3x2 + bx passes through (1, 2) :> 2 : a + b; y’ : 2ax + b and since the curve is tangent to y = x at the origin, its slope is 1 at x = 0 111 : y’:1whenx:0 =>1=2a(0)+b => b=1. Thena+b:2 :> a=l. Insummarya=b=landc=Oso the curve is y : x2 + x. 54. y=cx—x2 passes through (1,0) :> 0:c(1)—1 2 oz] :> the curve isyzx—xi’. For this curve, y’=1—-2xandx:1 :> y’: —l. Sincey=x—xzandyzx2+ax+bhavecommontangentsatx:O, y=x2+ax+bmustalsohaveslope~latx:1. Thusy’=2x+a => —1 :2-1+a => 21: ~3 => y = x2 —3x+b. Since thislast curve passes through (1,0), we haveO= l — 3+b :> b: 2. In summary, a:—3,b:2andc:—lsothecurvesarey:x2—3x+2andy:x—x2. 55. (a) y = x3 ~ x :5 y’ : 3x2 — 1. When x = —1, y : Oand y’ = 2 => the tangent line to the curve at(—1,0) is y=2(x+1)ory:2x+2i (b) _3 y—X—X ) y=2x+2 (c }=> x3—x=2x+2 => X3—3X—2=(X—2)(X+l)2=0 :> x:20rx:—1. Since y : 2(2) + 2 : 6; the other intersection point is (2, 6) 56. (a) y : x3 — 6x2 + 5x => y’ = 3x2 - 12x + 5. When x = 0, y = 0 and y’ = 5 :> the tangent line to the curve at (0,0) is y : 5x. ...
View Full Document

{[ snackBarMessage ]}